Microwave-assisted single-step synthesis of acid hydrazides from corresponding acids utilizing newly designed apparatus - Sabah Mohamad; Shaza Shantier; Elrashied Garalnabi (Journal of Applied Pharmaceutical Research, 2022)
Acid hydrazides are essential intermediates in organic synthesis. They conventionally require a two-step synthetic pathway; esterification and hydrazine hydrate treatment; to obtain the hydrazide. The microwave-assisted synthetic methodology was utilized as a greener and straightforward single-step approach for their synthesis in highly encouraging yields. Thus, the aim of the present work was to synthesize acid hydrazides of Diclofenac, Indomethacin, Ibuprofen, and Mefenamic acid using microwave radiation with the aid of a newly designed fit-in ice condenser. Esters of the selected compounds were firstly synthesized, and acid hydrazides were then synthesized utilizing both the conventional and the proposed microwave-assisted single-step methods. The developed technique was successfully yielded 86.7%, 40.9%, and 65.5% acid hydrazides of Diclofenac, Indomethacin, and Mefenamic acid in just 3 min., 10 min. and 3 min., respectively. In comparison to the conventional method, the developed method was simpler with a very short reaction time and quantified yields. The structures of the synthesized acid hydrazides were also confirmed using FT-IR and 1H-NMR. The proposed method with the modified fit-in ice condenser proved to be efficient, cost-effective, and time-saving in the synthesis of acid hydrazides understudy in a single step.